Pantanal flood pulse reveals constitutive and plastic features of two wild rice species (Poaceae, Oryzoideae): implications for taxonomy, systematics, and phylogenetics - Leandro, Thales D. [UNESP]; Manvailer, Vinicius; de Oliveira Arruda, Rosani do Carmo; Scremin-Dias, Edna (Springer Nature, 2022)
Annually, the Pantanal flood pulse induces the development of several plant structural responses, such as aerenchyma formation and differential lignification rates. Although such responses represent advantages for plants to thrive in flooded and non-flooded environments, the degree of variation often imposes limitations in identifying and establishing evolutionary relationships between allied species. Understanding the limits of plant plasticity is even more challenging for the Pantanal rice species, as they remain attached to a substrate during seasonal floods (emergent and/or epiphytic plants). The present study comparatively investigated the morphology and anatomy of the wild rice species Oryza rufipogon Griff. and O. latifolia Desv. throughout the Pantanal flood pulse to reveal their constitutive and plastic features. For this purpose, we studied qualitatively and quantitatively the leaf blades, culms, and roots of both rice species regarding environment and habit. While our results show a tremendous structural overlap between O. rufipogon and O. latifolia, leaf blade micromorphological and anatomical features are the most informative to recognize and classify the studied species. In contrast, the anatomical congruence of culms and roots is shared with many other grasses, thus lacking systematic significance. Culm and root length, aerenchyma formation and distribution, and lignification rates appear environment dependent. Indeed, the environment explains over 70% of the structural variation found in the present study. A set of life-form-specific structural features makes the epiphytic O. rufipogon readily distinguishable among emergent conspecifics and O. latifolia. We discussed implications for the taxonomy, systematics, and phylogenetics of Oryza, Oryzeae, Oryzoideae based on our results and literature reviews.
Keywords: Anatomy; Culm; Leaf; Morphology; Oryza; Root